A short review of our current understanding of the development of ring faults during collapse caldera formation - Geyer, Adelina; Martí, Joan (Frontiers in Earth Science, 2014)
The term collapse caldera refers to those volcanic depressions resulting from the sinking of the chamber roof due to the rapid withdrawal of magma during the course of an eruption. During the last three decades, collapse caldera dynamics has been the focus of attention of numerous, theoretical, numerical and experimental studies. Nonetheless, even if there is a tendency to go for a general and comprehensive caldera dynamics model, some key aspects remain unclear, controversial or completely unsolved. This is the case of ring fault nucleation points and propagation and dip direction. Since direct information on calderas’ deeper structure comes mainly from partially eroded calderas or few witnessed collapses, ring faults layout at depth remains still uncertain. This has generated a strong debate over the detailed internal fault and fracture configuration of a caldera collapse and, in more detail, how ring faults initiate and propagate. We offer here a very short description of the main results obtained by those analogue and theoretical/mathematical models applied to the study of collapse caldera formation. We place special attention on those observations related to the nucleation and propagation of the collapse-controlling ring faults. This summary is relevant to understand the current state-of-the-art of this topic and it should be taken under consideration in future works dealing with collapse caldera dynamics.